Dynamic capabilities and performance of family businesses in emerging economies - Rossignoli Cevallos, Gina; Guevara Sánchez, Daniel (Business: Theory and Practice, 2024)
Dynamic capabilities analyze the sources and methods of better performance and wealth creation and capture by firms operating in environments of rapid technological changes. Based on this, The objective of this research was to analyze the relationship between absorptive, adaptive, and innovation capabilities on financial and non-financial performance of family businesses was analyzed in the context of emerging economies, a relationship that has not been analyzed in this context. Through the application of structural equation modeling in a sample of 235 family businesses of agricultural supplies and machinery, located in the G46 and G47 categories of the International Standard Industrial Classification – ISIC, the results allowed us to identify that absorptive capability has a positive influence on financial performance, while innovation capability has a positive influence on no-financial performance. No evidence was found that other capabilities were related to the performance of the organizations analyzed. In addition, it was shown that the size of the companies does not generate any moderating effect in the relationship between these variables. This study contributes to dynamic capabilities theory by exploring how absorptive and innovative capabilities influence financial and non-financial performance in a specific and underexplored context: family businesses in emerging economies. Furthermore, the importance of developing and enhancing absorptive and innovation capabilities is highlighted. This could lead to the implementation of training programs, investment in R&D, and adoption of knowledge management practices.